Systematic Mapping Study on Serious and Educational Digital Games for the Prevention, Awareness, and Combating of Sexual Violence - Costa, Yan Oliveira da; Tomio, Vincent; Valentim, Natasha M. C. (Anais Estendidos do Congresso Brasileiro de Informática na Educação (CBIE); 2025: Anais Estendidos do XIV Congresso Brasileiro de Informática na Educação, 2025)
This paper aims to systematically identify and characterize existing serious and educational digital games focused on sexual violence, analyzing their narrative strategies, development methodologies, game mechanics, educational purposes, target audience, among other features. For this study, we defined database searches, such as IEEExplore, ACM, Scopus and ERIC. Eight papers were analyzed and revealed trends in game design, such as narratives including interactive storytelling and scenario-based learning. Limited long-term impact assessments and cultural adaptability were identified. These insights provide actionable recommendations for researchers, educators, and developers to enhance the efficacy of future games in this critical domain.